2D phase unwrapping system - Lee, Benjamin Juyi. (2009)
Phase unwrapping is an important but yet complex step in the phase extraction process. Phase extraction is used in many medical, military and industrial applications that involve digital image processing. The process of phase unwrapping is made further complicated by the presence of false phase wraps, caused either by noise or by the phase unwrapping algorithm itself. Phase unwrapping is also accumulative in nature with each image processed in a sequential fashion. Therefore false wraps may have adverse consequences on the results of the unwrapping process. Due to the sheer number of approaches and methods used to solve the problem, selecting a good algorithm or finding a good approach for a given situation can be challenging. Visualization for wrapped and unwrapped data is also vital in such a selection process. A visual system that can be used to compare the performance of these phase unwrapping can be useful in helping to make the final decision. Experiments were carried out to test effectiveness and speed of the different algorithms implemented in the system. The results of the experiments show that the algorithms are generally competent in unwrapping low to moderate noise data. Unwrapping data with high levels of noise continue to be challenging for these algorithms. Experiments revealed the exponential decrease in execution times these algorithms due to the increase in processing power available to us today. Algorithms that are complex or of combinatorial nature can be designed to harness the greater power of computer hardware that is available.